A Near-Run Thing: the Improbable Grand Alliance of World War II (1929–1942) - M. J. Carley (Концепт: философия, религия, культура, 2021)
This is a chapter from a draft manuscript of some 2000pp. in English being prepared for publication on relations between the USSR and various European powers, large and small, and the United States in the lead-up to World War II and then beyond until 1942. The author discovers and illustrates social and cultural aspects of diplomatic activities. The topic is Soviet relations with Nazi Germany and Poland in 1933. The larger context is the origins and unfolding of World War II, a subject of importance both intrinsically and politically in relations between the Russian Federation and the western powers. President Vladimir Putin has himself taken an interest in these questions, insisting on an honest, frank historical treatment of that period. How did the USSR and in particular the Narkomindel react to Adolf Hitler’s assumption of power in Germany at the end of January 1933? What additional information do the Russian archives contribute to our knowledge of the origins of the war? The methodology is that of a historical narrative based on archival research, especially in the AVPRF in Moscow. The objective is to explore the policies of the Narkomindel, and in particular the personal views of its leaders, M. M. Litvinov, N. N. Krestinskii, and B. S. Stomoniakov, on the interconnected issues of Soviet relations with Germany and Poland. Let’s call it an histoire des mentalités. 1933 was a year of transition in Soviet relations with the outside world moving from the so-called Rapallo policy of correct relations with Germany to a new policy of collective security and mutual assistance against Nazi Germany. In this chapter one can follow the evolution of ideas in the Narkomindel in reaction to Hitler’s rise to power: from immediate anxiety to a growing conviction that Rapallo was dead and that the USSR had to form stronger relationships in the west and with Poland. This may surprise some readers who think that the Soviet preference, or at least Stalin’s, was always a German orientation. As for Poland, in what may also surprise some readers, and especially many Poles, the Narkomindel sought better relations with Poland to counter the Nazi danger. It was the Polish government which did not want them, preferring a non-aggression pact with Nazi Germany (January 1934). Could Poles and Russians ever bury the hatchet after centuries of animosity? In a tragedy amongst many, they could not do so.